Poor pulmonary health in Barataria Bay dolphins in the eight years following the Deepwater Horizon oil spill - Smith, Cynthia R.; Rowles, Teresa K.; Gomez, Forrest M.; Ivančić, Marina; Colegrove, Kathleen M.; Takeshita, Ryan; Townsend, Forrest I.; Zolman, Eric S.; Morey, Jeanine S.; Cendejas, Veronica; Meegan, Jennifer M.; Musser, Whitney; et al. (Frontiers in Marine Science, 2022)
The Deepwater Horizon (DWH) disaster resulted in large-scale contamination of bays, sounds, and estuaries in the northern Gulf of Mexico, home to multiple stocks of common bottlenose dolphins (Tursiops truncatus). Inhalation, aspiration, ingestion, and dermal absorption of oil and its toxic components were all considered possible routes of exposure for dolphins living within the oil spill footprint. To determine if dolphins were adversely impacted, catch-and-release health assessments were performed in heavily-oiled Barataria Bay (BB), Louisiana, and in Sarasota Bay (SB), Florida, a comparison site with no DWH oil contamination. Initial studies were conducted as part of a Natural Resource Damage Assessment (2011-2014) and follow-on studies were performed between 2016-2018 with support from the Gulf of Mexico Research Initiative. Ultrasound was used to evaluate the dolphins’ pulmonary health, including the presence/absence of pleural effusion, nodules, masses, consolidation, and alveolar interstitial syndrome (AIS). When present, AIS was further graded by severity (mild, moderate, or severe) and distribution. Based on the presence and severity of abnormalities, each dolphin was given an overall lung disease score (normal, mild, moderate, or severe). Normal to mild scores were considered within expected limits for a wild population, therefore the prevalence of normal-mild versus moderate-severe scores was compared between the oiled and unoiled sites. Separate analyses were conducted for dolphins alive in 2010 (and in BB, presumably exposed to DWH oil), and those born after 2010. For the dolphins alive in 2010, temporal trends were also examined using generalized additive models (GAMs). Results showed a strong difference (p=0.000357) in moderate to severe lung disease between the two sites for dolphins alive in 2010, but no significant difference (p=0.6745) between the sites for dolphins born after 2010. In BB dolphins, the prevalence of moderate to severe lung disease did not decrease in the years after the spill, and in fact, potentially worsened (p=0.0644 for trend over years), with the highest prevalence (0.61) being in 2018. Moderate to severe AIS remained a persistent finding in BB dolphins, and several animals had a pattern of AIS that was more severe ventrally than dorsally, with evidence of chronic, progressive disease states.